So for this, I will be factoring by grouping. Firstly, what two terms have a product of -4x² and a sum of 3x? That would be -x and 4x. Replace 3x with -x + 4x:
![-x^2-x+4x+4=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/9tqnnb3funpbgzjrp3x15ix4fxnai40g6i.png)
Next, factor -x² - x and 4x + 4 separately. Make sure that they have the same quantity inside of the parentheses:
![-x(x+1)+4(x+1)=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/sjp57dm5qpkz7m4998arw025yptrxgk0vd.png)
Now you can rewrite the equation as
![(-x+4)(x+1)=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ynvjs4ele1o41hndeic4llv0hrw1rmluvg.png)
Now, apply the Zero Product Property to solve for x as such:
![-x+4=0\\-x=-4\\x=4\\\\x+1=0\\x=-1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ob4ilpkg1i15k7kz3qwwvekv4366r2rv48.png)
Your final answer is D. x = -1 and x = 4.